SOCIAL TRANSFORMATION OF WOTANMAS JEDONG VILLAGE COMMUNITY, MOJOKERTO REGENCY, 1980–2010: PERUBAHAN SOSIAL MASYARAKAT DESA WOTANMAS JEDONG KABUPATEN MOJOKERTO TAHUN 1980-2010 - Arjun Najach Alung Kibar; Aulia Fitriany; M Khusni Mubarok (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
The research to examine the dinamics of social change that occured in Wotanmas Jedong Village, Mojokerto Regency, during the period 1980-2010. This periode was chosen because it reflects a significant transition period, marked by the entry of industry, modernization, and the flow of globalization which influenced the economic structure and socio-cultural life of village communities. This research use histories method, field observation, in-depth interview, and literature study. The research result show that there has been a major transformation from a traditional agrarian sosiety to semi industrial society, which is characterized by a shift in livelihoods from the agricultural sector to the industrial and service sectors, an increase in education levels, and changes in people's values and lifestyles. Nevertheless, the community is still trying to preserve traditional values through the revitalization of local culture sich as the kenduren, selametan, and ruwat desa traditions. This finding shows that the modernization process does not completely erase local identity, but instead encourages communities to adapt and strengthen traditional values ​​in the context of changing times.